Презумпция вины, освобождение от гражданско-правовой ответственности и её исключение (Journal of actual problems of jurisprudence, 2019)
The article is devoted to the issue of the differentiation between such civil law institutions as release from liability and exclusion ofliability. The reasons for the release of liability are studied in the law theory, criminal and administrative law, and also within the civillegislation framework. The article speci fi es that the reasons for the exclusion of liability should be differentiated from the circumstancesthat exclude illegality of the action. Special attention is given to the issue of the general intent and no-fault liability